Issues of Good Governance of Pakistan: A Historical Analysis - Butt, Saima (Annals of Human and Social Sciences, 2024)
The idea good governance is not new to world history; in fact, it was in use in the state of Madina during the time of the Holy Prophet Muhammad and his four caliphs. The purpose of this article is to provide an overview of the main obstacles Pakistan has faced in meeting its governance standards over time.The idea of good governance is very recent, having only been introduced in the West in the 1980s. In this article I address what are the key economic, social, and political problems that Pakistan's bad governance stems from. A historical and descriptive method is used to examine the issue. Primary as well as secondary information both support the study.